2011
DOI: 10.1002/app.33539
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and rheology of composites based on anisotropic polymer matrix and different clays

Abstract: Structure and rheological properties of hybrids with polymer matrix and layered silicates as filler were studied. Solution containing 60% wt of hydroxypropylcellulose (HPC) in oligomeric polyethyleneglycol (PEG) was used as a matrix. The peculiarity of this study is that the matrix depending on temperature can form different phase states including liquid-crystalline (LC). So, a possibility of coexistence and superposition of different ordered structures can be realized at different temperatures. Three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…In this region, G * of composite SSPCMs exceeded 4–5 times that of the unfilled SSPCM. This result is consistent with that reported in ref ( 53 ), where it is shown that the degree of mechanical properties improvement induced by the incorporation of fillers into a liquid-crystalline matrix increases with the decrease of the matrix order. The carbonaceous fillers slightly affected the thermal stability of the SSPCM, causing melting temperature growth by ∼1.0° and 1.5 °C for SSPCM filled with MWCNTs and GnPs, respectively.…”
Section: Resultssupporting
confidence: 93%
“…In this region, G * of composite SSPCMs exceeded 4–5 times that of the unfilled SSPCM. This result is consistent with that reported in ref ( 53 ), where it is shown that the degree of mechanical properties improvement induced by the incorporation of fillers into a liquid-crystalline matrix increases with the decrease of the matrix order. The carbonaceous fillers slightly affected the thermal stability of the SSPCM, causing melting temperature growth by ∼1.0° and 1.5 °C for SSPCM filled with MWCNTs and GnPs, respectively.…”
Section: Resultssupporting
confidence: 93%
“…In this case, G ″ was higher than G ′, but the elastic modulus plateau appeared in the region of low frequencies, reflecting strong structuration in the system. This behavior is typical for filled polymer melts and solutions . Decreased G ′ values at high frequencies reflect weakening of the formed entanglement network, which can be attributed to a concentration drop of the dissolved polymer fraction.…”
Section: Resultsmentioning
confidence: 74%
“…This behavior is typical for filled polymer melts and solutions. 55 Decreased G′ values at high frequencies reflect weakening of the formed entanglement network, which can be attributed to a concentration drop of the dissolved polymer fraction. Figure 6 shows the evolution of shear viscosity (η) and elastic modulus (G′) with time for the 17 wt % HS dispersions.…”
Section: Biomacromoleculesmentioning
confidence: 98%
See 1 more Smart Citation
“…This W cg value represents that the bilayer structure of PEO or helical structure arranged in flattened arrangements can be accommodated because the trans ‐conformation of PEO chain has an expansion of about 0.4 nm . The intercalated 0.80 nm wide trans ‐gauche‐ trans double layers structures of PEO and poly(ethylene glycol) (PEG) are the most stable arrangement from steric consideration . Further increase of MMT concentration in the solution cast nanocomposite films, the observed W cg values range from 0.686–0.855 nm (Table ), which also confirms the existence of flattened bilayers arrangement of PEO structures in the MMT galleries.…”
Section: Resultsmentioning
confidence: 95%